Changes of Blood Pressure and Pulse Rate by Active Postural Changes in Early Brain Damaged Patients - FUTADA, MIKI; UEMURA, SACHIKO; SATAKE, MASAHIRO; ABE, NANAKO; ISHIZAWA, NOBUHIRO; MOMIYAMA, HIDEKI (Rigaku ryoho kagaku, 1998)
We carried out postural changes on three brain damaged patients in early period after onset and investigated changes in blood pressure and pulse rate measured at one heart beat intervals. Active postural changes were made every 3 minutes in the following order: supine position at rest, sitting upright, standing, sitting upright, and supine position. The results were that blood pressure and pulse rate increased going through the order of supine, sitting, and standing positions. However, blood pressure in the sitting position after the standing position was almost the same. Immediately after moving from the supine to the sitting position, and from the sitting to the standing position, blood pressure dropped momentarily and then showed a sharp increase, while pulse rate showed a sharp increase after which it declined a little. These changes were the same as those shown in healthy persons, and suggest the need for risk control in standing and sitting exercises for brain damaged patients in the early period after onset.